Redesigning blood pressure measurement training in healthcare schools. Issue 1 (31st December 2022) - Hayer, Rupinder; Kirley, Kate; Tsipas, Stavros; Allen, Jon; Hanson, Darlene; Johnson, Eric
ABSTRACT: Blood pressure (BP) measurement is the most commonly performed procedure in clinical practice and requires mastering several skills. A prior study determined that medical school students failed to perform more than half of BP measurement skills correctly, demonstrating a need to redesign how BP measurement is taught. The American Medical Association set out to create and test a solution to address this BP measurement curricula gap. An eLearning series consisting of three modules was developed. The series was informed by evidence-based guidelines, includes content on self-measured blood pressure, is accessible to students at any time within their education journey, is interactive, and available to all healthcare schools at no cost. Prior to launch, a small pilot study was conducted with medical and nursing students to determine if these new eLearning modules address current gaps in BP measurement curricula. Students were instructed to complete an online assessment before and after viewing the main module within the series. Our results suggest that eLearning modules on BP measurement can help improve knowledge and ability to identify correct BP measurement skills. Pronounced improvements were observed in the topics of patient preparation, positioning, and cuff sizing and placement. Revisions were made to content areas where improvement was minimal. Overall, the findings revealed the importance of pilot testing a product prior to launch and while many skills may improve with an eLearning intervention, certain skills will still likely require additional in-person training with peers.